The Debate on the International Monetary System - Mateos y Lago, Isabelle (IMF Staff Position Notes; Staff Position Note, 2009)
This paper considers options to address concerns related to functioning of the International Monetary System. Despite its relative stability, the current 'non-system' has the inherent weaknesses of a setup with a dominant country-issued reserve currency, wherein the reserve issuer runs fiscal and external deficits to meet growing world demand for reserve assets and where there is no ready mechanism forcing surplus or reserve-issuing countries to adjust. The problem has amplified in recent years in line with a sharp rise in the demand for reserves, reflecting in part emerging markets' tendency to self-insure against costly capital account crises. On the demand side, the paper explores alternative insurance arrangements that could mitigate the precautionary demand for reserves. On the supply side, it assesses a menu of alternative reserve assets that could offer sustained stability and efficiency. Many of the proposals presented would require fundamental changes in the forms and degree of international cooperation, however, may gain realism and practical relevance if more incremental efforts at strengthening the current system fail.